Molekular Docking Senyawa Analog Kalkon sebagai Inhibitor untuk Sel Kanker Paru-Paru A549 - Neni Frimayanti; Meiriza Djohari; Alifah Nurul Khusnah (JURNAL ILMU KEFARMASIAN INDONESIA, 2021)
Chalcones are compounds derived from nature, it is show the anticancer activity. The aim of thisstudy is to determine the binding free energy (affi nity) and interaction of chalcone derivatives as inhibitors for A549 lung cancer cells using 4HFZ protein as receptors. This study used 10 chalcone derivatives which were selected with three lowest IC50 values, fi ve medium IC50 values and two with higher IC50 values (i.e. more than 100 μg/mL) and 4HFZ protein was used as receptor. The structure of the chalcone derivative is transformed in 3D structure, then the docking process of chalcone compounds with amino acids on the MDM2 receptor (4HFZ) is carried out. The simulation results shown that data in the form of binding free energy value (kcal / mol) shown the stability of ligand interaction of chalcone compounds on amino acids on MDM2 receptors. The docking results shown that, compound 2 is able to bind strongly with MDM2 receptor (4HFZ) and it is also stable because it has a low binding-free energy value of -7.2 kcal / mol, with a RMSD value of 0,000. Construction of some hydrogen bonds is the same as active receptor (gefi tinib), they are Leu54 on the NH2.